การคำนวณเครื่องปฏิกรณ์นิวเคลียร์แบบใช้น้ำธรรมดา ในส่วนที่เกี่ยวกับนิวตรอนโดยใช้โปรแกรมคอมพิวเตอร์ - ดรุณี สุวิทยพันธุ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
This Thesis concerned about burnup and criticality calculation in light water reactor with fuel composing of uo₂, Tho₂, Puo₂, uo₂-Tho₂, or Puo₂ - uo₂ using computer program "RISOT-5". In this program, neutron energies are divided into 5 non-overlapping groups (three fast groups and two thermal groups) and reactor core composing of identical unit cells. Neutron transport theory was used primarily in unit cell calculation and homogenization factors were obtained. The factors will be used for evaluating nuclear constants in homogenized core. Burnup and criticalities at any time in loading reactor were calculated by using two groups (one fast group and one thermal group) diffusion theory and assuming the usual point reactor model. For a burnup calculation, 21 time steps using IBM 370/138, the calculation time was 23 seconds.